Dimensional crossover for universal scaling far from equilibrium - Gresista, Lasse; Zache, Torsten Victor; Berges, Jürgen (Physical review, 2022)
We perform a dynamical finite-size scaling analysis of a nonequilibrium Bose gas which is confined in the transverse plane. Varying the transverse size, we establish a dimensional crossover for universal scaling properties far from equilibrium. Our results, which are based on classical-statistical real-time lattice simulations, suggest that some aspects of the dynamical universal behavior of anisotropic systems can be classified in terms of fractional spatial dimensions. We discuss our findings in view of recent experimental results with quasi-one-dimensional setups of quenched ultracold quantum gases.